2011
DOI: 10.1152/ajprenal.00139.2011
|View full text |Cite
|
Sign up to set email alerts
|

Fetal uninephrectomy in male sheep alters the systemic and renal responses to angiotensin II infusion and AT1R blockade

Abstract: Fetal uninephrectomy (uni-x) at 100 days of gestation results in compensatory nephrogenesis in the remaining kidney, resulting in a 30% reduction in total nephron number in male sheep. Recently, we showed that uni-x males at 6 mo of age have elevated arterial pressure, reduced renal blood flow (RBF), glomerular filtration rate (GFR), and low plasma renin levels (Singh R, Denton K, Bertram J, Jefferies A, Head G, Lombardo P, Schneider-Kolsky M, Moritz K. J Hypertens 27: 386-396, 2009; Singh R, Denton K, Jefferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 50 publications
4
21
3
Order By: Relevance
“…We have also recently reported that basal plasma renin and ANG II and renal tissue renin and ANG II levels are significantly reduced in 6-mo-old uni-x male sheep as are levels of both ANG II receptors (AT1R and AT2R) (33). Additionally, we showed that in response to increases in arterial pressure induced by exogenous ANG II infusion, uni-x male sheep exhibited a paradoxical increase in GFR, suggesting the renal autoregulatory mechanisms that usually buffer the kidney against fluctuations in arterial pressure were perturbed in these uni-x animals (33).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…We have also recently reported that basal plasma renin and ANG II and renal tissue renin and ANG II levels are significantly reduced in 6-mo-old uni-x male sheep as are levels of both ANG II receptors (AT1R and AT2R) (33). Additionally, we showed that in response to increases in arterial pressure induced by exogenous ANG II infusion, uni-x male sheep exhibited a paradoxical increase in GFR, suggesting the renal autoregulatory mechanisms that usually buffer the kidney against fluctuations in arterial pressure were perturbed in these uni-x animals (33).…”
Section: Discussionmentioning
confidence: 62%
“…We have previously reported that fetal uni-x in male sheep results in an approximate 30% reduction in nephron number at the completion of nephrogenesis due to compensatory nephrogenesis in the remaining kidney (15). Male uni-x sheep have low plasma renin levels, elevated arterial pressure, and reduced glomerular filtration rate (GFR) and renal blood flow at 6 mo of age (15,(31)(32)(33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This could arise if ANG II were to increase sodium reabsorption, or to reduce the efficiency of oxygen utilization for sodium reabsorption in the medullary thick ascending limbs and/or the distal nephron. Such effects are likely, given that 1) glomerular filtration rate is better maintained than RBF during infusion of ANG II in conscious sheep (27) and 2) ANG II stimulates superoxide production and thus sodium reabsorption in the thick ascending limb (22). On the other hand captopril increased RBF and renal oxygen consumption, but despite this hyperemia there were no significant changes in cortical or medullary LDF or tPO 2 .…”
Section: Discussionmentioning
confidence: 98%
“…In F2 Control and Restricted rats studied to 6 months, renin activity, angiotensin II (AngII) and angiotensin 1-7 (Ang1-7) content were analysed in plasma in frozen renal cortices using radioimmunoassay techniques (Prosearch International, Malvern, Vic., Australia; Singh et al 2011).…”
Section: Intra-renal and Plasma Renin-angiotensin System (Ras) Componmentioning
confidence: 99%